Budgeting in Latvia - Kraan, Dirk-Jan (OECD Publishing, 2010)
At the time of this review, fiscal policy in Latvia was in considerable turmoil as a consequence of the world-wide financial crisis. Thus, some of the usual budget rules and procedures were not followed during budget preparation 2009 and 2010 and budget execution 2009. This review examines the usual budget rules and procedures that were followed until 2008 and also the major institutional revisions that were discussed in 2009. The instability of fiscal policy is a major problem for Latvia and there is an urgent need to bring more stability to the budget process